2020
DOI: 10.1155/2020/9472656
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Mechanical Properties and Acoustic Emission Characteristics of Water Bearing Sandstone under Stable Cyclic Loading and Unloading

Abstract: Due to the adjustment of energy structure, a large number of coal mines are abandoned. Considering the environmental and economic effects, many experts proposed to use the abandoned mine cavern as the reservoir of the pumped storage power station. Furthermore, considering the long-term effects of repeated pumping and drainage and hydrodynamic pressure on the surrounding rock in coal mines, a large amount of sandstone was collected from the Ruineng coal mine in Yan’an city to carry out a series of laboratory te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…When the rock was in the elastic stage, the acoustic emission ring count entered a brief stable period. As the load increased beyond the previous target stress level, the acoustic emission ring count showed an increasing trend and exhibited a pronounced Kaiser effect [10]. When the rock reached its peak strength, the acoustic emission signals became dense, with a maximum ring count of 3745 and an acoustic emission energy of 3.0 × 10 8 .…”
Section: Acoustic Emission Ring Count and Energy Count Characteristic...mentioning
confidence: 97%
See 1 more Smart Citation
“…When the rock was in the elastic stage, the acoustic emission ring count entered a brief stable period. As the load increased beyond the previous target stress level, the acoustic emission ring count showed an increasing trend and exhibited a pronounced Kaiser effect [10]. When the rock reached its peak strength, the acoustic emission signals became dense, with a maximum ring count of 3745 and an acoustic emission energy of 3.0 × 10 8 .…”
Section: Acoustic Emission Ring Count and Energy Count Characteristic...mentioning
confidence: 97%
“…Liu et al [9] studied the mechanical properties of sandstone under triaxial cyclic loading and used the cumulative dissipated energy damage variable theory to analyze the increase in the damage variable with the increase in cyclic loading stress. Qin et al [10] studied the mechanical properties and acoustic emission characteristics of sandstone under cyclic loading and unloading, finding that an increase in the number of cycles improved the elastic modulus of rocks with a gradual decrease in the Felicity ratio. Zou et al [11] investigated the energy evolution laws of hexagonal honeycomb structures under different graded cyclic loading and unloading patterns, reflecting the exacerbation of internal rock damage with increased upper and lower bounds of cyclic loading and unloading.…”
Section: Introductionmentioning
confidence: 99%
“…Lavrov [6] studied the effect of the loading rate on rocks in complex stress paths and found that the acoustic emission activity of rocks was intense at high loading rates. Jiang et al [7] conducted experiments on the stress-strain relationship and acoustic emission characteristics of dense granite and marble under different loading rates and revealed the effects of the loading rate on stones. Cong Yu et al [8] studied the fracture morphology and cracked extension of rocks by constructing the specimen geometry, contacting intrinsic formation interaction, and iterative analysis to make the macroscopic mechanical properties of numerical specimens close to those of natural materials.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [13] pointed out AE activities could be divided into compaction and elastic deformation, non-elastic deformation and fracturing failure phase and proposed a new damaged model to describe the coal damage. Qin et al [14] carried out the uniaxial compression mechanical and AE tests of rock samples with different moisture content and clarified the influence of moisture content on AE characteristics. Teng et al [15] analyzed the mechanical and AE characteristics of dry and saturated sandstone under different loading rates.…”
Section: Introductionmentioning
confidence: 99%